TEORI PSIKOSOSIAL ERIK H. ERIKSON DAN RELEVANSINYA TERHADAP PENDIDIKAN ANAK USIA DINI - Rita Kencana (QURROTI, 2024)
The Psychosocial Development Theory proposed by Erik Erikson has made an important contribution to the world of Early Childhood education. Some of the developmental stages described by Erikson are certain to be passed by each individual throughout his or her life, although not everyone can deal with them perfectly. This theory makes a significant contribution to early childhood education, although it is not the only theory that should be considered in educational planning, especially at an early age. This article will review several stages of psychosocial development and their relevance to early childhood education. This study uses a literature study method, namely by collecting and analyzing library data into a research. The conclusions obtained show that to achieve optimal psychosocial development, the role of family, school, children's living environment, peers, as well as factors of self-maturity, social status, mental capacity, emotional development, and intelligence level are needed. Early childhood experiences of social interaction in family, school, and with peers also greatly influence the way they behave towards others in society. Therefore, the family is not only the main place to shape children's social interactions, but also plays a role in instilling norms and interaction skills. It is hoped that children will be aware of their role and feel accepted in the environment where they live, which in turn will have a positive impact on social, emotional, and other developments.